Preliminary insights from the Philippine Bureau of Customs imports database - Mendoza, Ronald U (Archīum Ateneo, 2015)
This paper provides an analysis of recently released importation data by the Philippine Bureau of Customs (BOC). The dataset has been released as part of the government’s open data and transparency reforms aimed at boosting good governance and reducing corruption. The dataset includes information on over 88,000 imported items in December 2013, such as a description of the item imported, its HS code number and standard HS code description, what country the item came from, its value, and the amount of duties and taxes collected on that item. The BOC released the data along with a call for the public to assist by helping to analyse the dataset and (where necessary) report data discrepancies noted between the import valuation recorded in the dataset and those used in practice. The paper presents a preliminary analysis of the data released by the BOC and provides a platform to understand issues surrounding Philippine customs operations and reforms.